Adhesive and Injectable Hydrogel Microspheres for Inner Ear Treatment. Issue 36 (1st February 2022) - Chen, Kaili; Wang, Fei; Ding, Rui; Cai, Zhengwei; Zou, Tianyuan; Zhang, Andi; Guo, Dongye; Ye, Bin; Cui, Wenguo; Xiang, Mingliang
Abstract: The least damaging and most economical method to deliver drugs or carriers into the inner ear for treatment of disease is through the middle ear. However, the retention of drug in the middle ear is an obstacle. Here, inspired by the adhesion of mussels, a methacrylate gelatin microspheres (GM) coupling polydopamine (PDA) layer (GM@PDA) with excellent adhesive ability is constructed, and Ebselen liposomes are further loaded into the GM@PDA (GM@PDA@Lipo‐Ebselen). The loading capacity of GM@PDA for Ebselen liposomes is 25 ± 1 µg mg −1 microspheres. GM@PDA@Lipo‐Ebselen could be injected on round windows membrane (RWM) and tightly adheres to the surface of RWM by PDA, and the microspheres are even still attached to the RWM after 360° rotation and inverted shaking. The in vivo imaging system shows that the adhesive microspheres can prolong the retention of the middle ear cavity for more than 7 days. The hearing of mice in the GM@PDA@Lipo‐Ebselen group is significantly recovered, especially on day 14 after noise exposure, and the hearing of each frequency is restored to baseline level. At 32 kHz frequency, the survival of outer hair cells recovers from 48 0± 6% to 93 ± 2%. Therefore, the adhesive and injectable hydrogel microspheres provide a promising strategy for the treatment of hearing loss. Abstract : A mussel‐inspired injectable hydrogel microsphere loading Ebselen liposomes which adheres to cochlea round windows membrane (RWM) is constructed. The positively charged primary amine groups through electrostatic interaction and the catechol groups through high‐strength coordination bonds and hydrogen bonds adhere to the RWM. This adhesion can prolong the retention of the middle ear cavity and helps with inner ear therapy.